ISOLASI DAN KARAKTERISASI BAKTERI ASAM LAKTAT PADA PANGAN FERMENTASI MANDAI - Mangasa Tua Pandapotan Siregar; Endang Kusdiyantini; MG Isworo Rukmi (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
East Kalimantan has a lot of processed food products traditionally, one of them is mandai which is fermented food made from fruit leather Cempedak (Arthocarphus champeden). Lactic acid bacteria involved in the fermentation mandai greatly affect the quality of the final product. This study aimed to perform the isolation and characterization of lactic acid bacteria in the mandai fermentation process. MRS medium was used in the isolation of bacteria for 14 days. Isolation of bacteria during the fermentation process mandai obtaining 17 isolates, nine isolates Gram negative isolates, and eight isolates Gram positive. Eight isolates showed positive results against some of the morphological and biochemical characterization. Including biochemical characterization, acid formation and gas production from glucose, motility test, catalase test, growth at 160C and 480C, hydrolysis of starch, fat hydrolysis, and hydrolysis of casein and acid formation test. Eight isolates bacteria made mandai into processed food products that had a sour taste. Keywords: lactic acid bacteria, BAL ,bacterial isolates, cempedak skin.